Stereotyped Molecular Response During Liver and Kidney Ischemia/Reperfusion Injury. (July 2018) - Bontha, Sai Vineela; Gehrau, Ricardo; Fernandez, Angela C; Bardhi, Elissa; Cho, Brandon; Maluf, Daniel G.; Mas, Valeria R
Abstract : Background: Ischemia reperfusion (I/R) injury is one of the major contributors to short-term graft function. Dissecting organ specific pathways and common molecular pathways associated with I/R injury among different organ types will help in better designing of specific therapeutic interventions. It will also help in understanding tissue specific injury and recovery mechanisms following early I/R injury. Methods: 120 Gene expression (Affymetrix HG-U133Av2 Gene Chips) arrays were performed on allograft biopsies obtained from deceased donor kidney transplant recipients (n = 30) and liver transplant recipients (LTRs) (n = 30). From each patient, pre-implantation (PI) and post-reperfusion (PR) biopsies were obtained. Gene expression analysis was done using expression and transcriptome console softwares. PI and PR gene expression was compared in liver and kidney biopsies separately and probe sets were considered significant when the false discovery rate (FDR) was < 5 % and fold change greater than 1.5. IPA software and other gene enrichment and cell type enrichment softwares were used for further analysis of the data. Results: Comparing gene expression in PI and PR biopsies from LTRs resulted in 438 probe sets and similar analysis in KTRs yielded 366 differentially expressed probe sets. Upon comparing the early I/R response in Liver and Kidney, it was observed that 40 – 50 % of the differentially expressed genes were similar in both organs and these genes were mainly involved in inflammatory pathways and transcription regulation. Around 28% of the common genes were transcription factors and around 12% were cytokines and growth factors. Among the top common pathways were IL6 signaling pathway, NF-KB signaling, HMGB1 signaling, and production of NO and ROS in macrophages. However, the main differences associated with liver specific I/R response genes involving growth factors and cytokines that relate to wound healing and additional reparative processes like angiogenesis. Also, additional molecular pathways involved in functions like T cell development, lymphopoiesis and response of neutrophils were exacerbated in the liver tissues. Otherwise, in kidney tissues undergoing I/R the initial unique molecular pathways were those involved in inhibition of growth of connective tissue Conclusion: We identified common intra-allograft inflammatory responses to I/R injury between kidney and liver transplantation. However, liver grafts presented a faster activation of molecular profiles associated with regenerative, reparative and growth factors related functions.